1983
DOI: 10.1071/ar9830053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced variance due to selection in open nucleus breeding systems

Abstract: In the design of breeding programs the consideration of open nucleus breeding systems may result in a useful alternative. The available theory dealing with these systems assumes constant parameters, but a more exact approach would take into account the possible changes in genetic variance. Numerical evaluation of formulae allowing for loss of genetic variance due to linkage disequilibrium and increase of variance due to mixing groups with different breeding values, suggests that optimum transfer rates, as pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The difference between annual genetic gain observed in the nucleus and in the base was −96, − 1, 18 and 11 for G1, G2, G3 and G4, respectively. This result is in agreement with the findings of Mueller and James (1983). They reported that the cumulated gain after 10 generations of selection, in a likely sheep or cattle system, would be overestimated by about 20%.…”
Section: Number Of Generations (G)supporting
confidence: 94%
“…The difference between annual genetic gain observed in the nucleus and in the base was −96, − 1, 18 and 11 for G1, G2, G3 and G4, respectively. This result is in agreement with the findings of Mueller and James (1983). They reported that the cumulated gain after 10 generations of selection, in a likely sheep or cattle system, would be overestimated by about 20%.…”
Section: Number Of Generations (G)supporting
confidence: 94%
“…The scaling factor 0-8 is included to account approximately for the reduction in genetic variance due to selection, the so-called 'Bulmer effect' (Bulmer, 1971). Mueller and James (1983) found that allowance for the Bulmer effect reduced predicted gains proportionately by around 0-2 for open nucleus schemes, but had very little effect on the optimal design or ranking of alternatives, which justified the use of a simple scaling factor. Mueller and James (1983) found that allowance for the Bulmer effect reduced predicted gains proportionately by around 0-2 for open nucleus schemes, but had very little effect on the optimal design or ranking of alternatives, which justified the use of a simple scaling factor.…”
Section: Methodsmentioning
confidence: 99%
“…This is a temporary reduction caused primarily by gametic phase or linkage disequilibrium and is counteracted by free recombination at meiosis (Mendelian sampling), and a balance is reached after a few generations. The magnitude of the decrease in variance due to selection depends on the initial narrow-sense heritability, selection accuracy and intensity (among others Bulmer 1971;Mueller and James 1983b;Wray and Hill 1989;Gomez-Raya and Burnside 1990). Consequently, under strong selection, there will be a substantial decrease both in BP response over the first generations and in the additional gain available from PPs.…”
Section: Effect Of Selection and Mating On Genetic Variancementioning
confidence: 97%
“…In contrast, for situations with low heritability or low selection precision, progress from withinfamily selection is less and relatively more is gained from unbalanced parental contributions (Rosvall and Andersson 1999). However, if family variance is exploited there are large losses in both among-family variance (Bulmer 1971;Mueller and James 1983b;Wray and Hill 1989;Gomez-Raya and Burnside 1990) and within-family variance (Verrier et al 1989(Verrier et al , 1990(Verrier et al , 1991.…”
Section: Realised Production Population Gainmentioning
confidence: 98%